Iniciação científica na Amazônia: bases históricas e epistemológicas dos clubes de ciências de Abaetetuba- PA e Moju- PA - CAJUEIRO, Dayanne Dailla da Silva (Universidade Federal do Pará, 2022)
Scientific initiation, scientific dissemination, scientific culture, science fairs, initial and continuing education for teaching... These are some of the actions that have been developed by Science Clubs in Pará. The first Science Club emerged in mid-1979 in the state, called Science Club of the Federal University of Pará - CCIUFPA and since then its actions have contributed to the dissemination of several other spaces in neighboring municipalities and in distant regions of the state that have been consolidated with personality and identity, therefore, although the actions move towards the same objective, which is the scientific initiation of professors and students, these Clubs were encouraged to develop and constitute themselves based on the demand of their public and community, which makes them unique within their operating context. In this research, focus is given to the historical and epistemological bases of the scientific initiation of the Science Clubs of Abaetetuba-PA and Moju-PA. In this direction, the research problem is expressed: "in what terms are the activities of Science Clubs in the immediate geographic region of Abaetetuba-PA configured, in view of the historical-epistemological bases of scientific initiation developed by them?", and how objective: to investigate the epistemological historical bases of the scientific initiation activities of these spaces mentioned there, from the investigated histories from its foundation to the present day. In this perspective, I defend the thesis that the Science Clubs of Moju-PA and Abaetetuba-PA build and develop pedagogical practices in line with the demands of contemporaneity, whose historical, theoretical-methodological and epistemological aspects of scientific initiation are predominantly located in the development cultural center focused on the ScienceKnowledge-Society trilogy, contributing to the formation of critical and responsible citizenship for students and the professional development of teachers. For this, I adopt qualitative research in the narrative modality, where life experiences of students, teachers, coordinators and collaborators of these spaces are intertwined in information documented in scientific works and internal records (from minutes of meetings, scientific initiation projects, histories, among others. others.) constituting oral and written narratives. In this sense, for the analysis of the information, I adopt the discursive textual analysis and in this way, the raised narratives were constituted in field texts that from new and other interpretations form this metatext. From this analysis, I build three emerging axes: i) “TAKING FORWARD THE AFFLUENTS: consolidation of the Science Clubs of MojuPA and Abaetetuba-PA”; ii) “THIS RIVER IRRIGUATED CULTURE: dissemination and popularization of Science”; iii) “THE WATERS CHANGE: different contexts of scientific initiation in basic education through the Science Clubs of Abaetetuba and Moju for the 21st century”; The results show that the Science Clubs of Moju-PA and Abaetetuba-PA build and develop pedagogical practices according to contemporary demands, where the historical aspects of scientific initiation are located in cultural, educational, technological and Science development, thus contributing way, for the critical formation of the citizen and for the teaching professionalization. In this way, I conclude that studying scientific initiation in Science Clubs, through narratives, is to retake the experience, relive stories lived and told by those who look at Science and its teaching with new perspectives for basic education, thus recounting the history of Science in the educational scope projecting new perspectives for the formation of the citizen of this century in the context of Pará and in the country.